Synthesis of Gold Nanoparticles Using Lamellar Liquid Crystal of Protic Ionic Liquids - Li, Qiuhong; Li, Aixiang (Asian Journal of Chemistry, 2011)
Gold spherical nanoparticles and nanoplates with triangular, pentagonal or hexagonal shapes are synthesized by reduction of H[AuCl4] in lyotropic liquid crystal (LLC) mainly made of poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) block copolymers and protic ionic liquids (PILs) [Pyrr][NO3]. Lyotropic liquid crystal was characterized by small-angle X-ray scattering measurements. Transmission electron microscopy and UV-VIS spectroscopy show the formation of spherical nanoparticles and nanoplates.